2020
DOI: 10.1002/ps.5748
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and functional expression of voltage‐gated sodium channel variants in Apolygus lucorum (Meyer‐Dür)

Abstract: BACKGROUND: Apolygus lucorum (Meyer-Dür) is a serious worldwide agricultural pest, especially for Bt cotton in China. Pyrethroids, neonicotinoids and organophosphates are the most effective insecticides to control piercing and sucking insects, including A. lucorum. The voltage-gated sodium channel (Na v ) is major target site of pyrethroids. Extensive alternative splicing and RNA editing, two major post-transcriptional mechanisms, contribute to generate different functional sodium channel variants. In our rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…MpNa v ‐II contains a pair of mutually exclusive exons k/l, and only exon l is related to increased neural activity. However, exon k is not included in Acyrthosiphon lucorum 13 . Exons k/l are highly conserved in sequence and genomic structure among insect species, but in modulating sodium channel function, exon k‐containing variants exhibit a high level of resistance to pyrethroid insecticide in Nilaparvatal lugens 45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MpNa v ‐II contains a pair of mutually exclusive exons k/l, and only exon l is related to increased neural activity. However, exon k is not included in Acyrthosiphon lucorum 13 . Exons k/l are highly conserved in sequence and genomic structure among insect species, but in modulating sodium channel function, exon k‐containing variants exhibit a high level of resistance to pyrethroid insecticide in Nilaparvatal lugens 45 .…”
Section: Discussionmentioning
confidence: 99%
“…cloned the first insect Na v from Drosophila melanogaster 11 . With the improvement of sequencing technologies, an increasing number of insect Na v s , such as Bombus spp., Apolygus lucorum (Meyer‐Dür), Blattella germanica , and Myzus persicae (Sulzer), has been identified 12–15 . Na v s widely exist in animals, but their number varies remarkably 3,16 .…”
Section: Introductionmentioning
confidence: 99%
“…18 Our group successfully cloned and expressed AlNa v in Xenopus oocytes. 23 In this study, we found double mutations L 1002 F and M 906 I (L 2i16 F and M 2k11 I) which are in the domain II from field population of A.lucorum in China (L 1002 F in our research is the same amino acid position as L 1015 F in Zhen's research, for different variants). Although the double mutation was conferred to pyrethoids resistant in other insect species, we still need directly to prove the function of L 1002 F/ M 906 I in A. lucorum.…”
Section: Introductionmentioning
confidence: 47%
“…Zhen reported a population collected from Shandong Province that exhibited 30‐fold resistance to λ‐cyhalothrin, and mutation L 1015 F was detected only in the Shandong population in the AlNa v (sodium channel in A. lucorum ) 18 . Our group successfully cloned and expressed AlNa v in Xenopus oocytes 23 . In this study, we found double mutations L 1002 F and M 906 I (L 2i16 F and M 2k11 I) which are in the domain II from field population of A.lucorum in China (L 1002 F in our research is the same amino acid position as L 1015 F in Zhen’s research, for different variants).…”
Section: Introductionmentioning
confidence: 99%
“…We adhered scrupulously to the rules for animal welfare and protection set forth by China, Hainan University, and international norms. Oocyte preparation, cRNA production, and injection techniques were the same as previously described . cRNA was created utilizing the mMESSAGE mMACHINE high-yield capped RNA kit and in vitro transcription with T7 polymerase (Ambion, Austin, TX, USA).…”
Section: Methodsmentioning
confidence: 99%